Anti-Inflammasome Effect of Impressic Acid on Diesel Exhaust Particulate Matter-Induced NLRP1 Inflammasome via the Keap1/p62/Nrf2-Signaling Pathway in Keratinocytes - Seung Yeon Lee; Gi Ho Lee; Jeonghwan Maeng; Su Yeon Kim; Hwi-Yeol Yun; Gil-Saeng Jeong; Hye Gwang Jeong (Antioxidants)
Diesel exhaust particulate (DEP) is widely recognized to weaken lung function and skin diseases. When the skin, which defends against external factors, is exposed to PM2.5, various chronic inflammatory diseases occur. When keratinocytes recognize harmful signals, they synthesize the NOD-like receptor protein 1 (NLRP1) inflammasome. DEP enhances NF-κB signaling and NLRP1 inflammasome expression through the interaction of TXNIP with NLRP1 in keratinocytes. Although many studies have reported the anti-inflammatory and antioxidant characteristics of Impressic acid (IPA), the umbrella consequences of IPA for PM2.5-influenced inflammasomes and the associated mechanisms remain unknown. Therefore, this study aimed to examine the protective function of IPA against inflammation in human keratinocytes. IPA attenuated the NLRP1 expression, caspase-1, IL-1β actuation, and NF-κB and IκB phosphorylation induction by DEP. IPA upregulated the Nrf2, HO-1, and NQO1 expression through CaMKKβ, AMPK, and GSK3β phosphorylation. Also, IPA led to the elevation of p62 and the degradation of the Keap1 protein. ML385 reversed the suppressive effect of IPA on the NLRP1 inflammasome, which was enhanced by DEP, and NAC counteracted the effect of ML385. These findings indicate that IPA can suppress inflammation induced by PM2.5 by expressing antioxidant enzymes through the Keap1/p62/Nrf2-signaling pathway in human keratinocytes.